Komparasi Motif Lukisan Kulit Kayu Asei Dari Masa Lalu Hingga Masa Kini: Perkembangan Lukisan Kulit Kayu Sejak Abad ke-20 Hingga Masa Kini di Kampung Asei, Sentani, Papua - Putri, Amurwani; Suroto, Hari; Sudarmika, Gusti Made (Berkala Arkeologi, 2025)
In human life, the development of ideas through painting has been done since ancient times. Symbols and strokes are believed to be a means of conveying messages. The expression of the painting is applied to natural canvases such as cave walls, large rocks, and even bark. In the community of Asei village, Sentani, a painting in the past was applied to the clothes of a Ondoafi made of bark. The painting reflects their lives and their beauty.  This paper aims to explain the research results on the shift in nature, meaning, and function of Asei bark paintings in the 20th Century to the present. The research method is descriptive qualitative with an ethnoarchaeological approach. The result indicates that bark paintings are no longer only considered as works of art, but also as a supporter of the family economy, as well as being a distinctive product of Asei, Sentani, commercial in nature.